Deciphering Celebrity Worship Phenomenon: Simulation and Analysis using SFR Mathematical Model with Time Delay among Fans in South Sulawesi - Arsita, Asriani; Minggi, Ilham; Pandjajangi, Andi Muhammad Ridho Yusuf Sainon Andi; Side, Syafruddin; Arwadi, Fajar (Journal of Mathematics, Computations and Statistics, 2024)
This study explores the mathematical SFR model to analyze Celebrity Worship Behavior among devoted K-Pop fans. Primary data were collected through questionnaires distributed within the South Sulawesi Province, providing insights into the dynamics of Celebrity Worship Behavior among K-Pop enthusiasts. The research involves developing an SFR model with time delays, followed by a series of analyses and simulations related to Celebrity Worship Behavior in the K-Pop community. This comprehensive approach includes identifying equilibrium points, evaluating model stability, calculating the basic reproduction number (R0), conducting simulations using Maple software, and interpreting the simulation results. The SFR mathematical model reveals two equilibrium points: one representing the baseline level of Celebrity Worship Behavior among K-Pop fans and the other specific to this behavior. The calculated R0 value of 0.425 suggests a potential decrease in the prevalence of Celebrity Worship Behavior within the K-Pop community.